Validation method for design of system security of AltaRica model - HU JUN; CHEN SONG; WU ZHIPENG (2016)
The invention discloses a validation method for design of system security of an AltaRica model. The method comprises following steps: step 1, establishing an AltaRica model for design of system security; step 2, defining the rule for model transformation from the AltaRica model to a Promela model; obtaining the Promela model after conversion of the AltaRica model; step 3, utilizing lineal temporal logic to describe the system security demand in a formalized manner; step 4, utilizing a model detector to validity security of a system model; step 5, obtaining a security demand counter-example that does not satisfy the step 4, tracking the system security design model and finishing validation of the system security design model.The validation method for design of system security of the AltaRica model has following beneficial effects: a model conversion problem is effectively solved; operation on AltaRica is conducted by a model detection tool SPIN; and the validation method provides a new way of thinking for anal